2004
DOI: 10.1002/glia.20131
|View full text |Cite
|
Sign up to set email alerts
|

Glial transcytosis of a photoreceptor‐secreted signaling protein, retinoschisin

Abstract: In vitro studies have clearly shown that signaling/guidance proteins can diffuse to their targets. However, it is unclear whether they can travel by diffusion in vivo, or if they are distributed in the tissue by an active mechanism. Retinoschisin, a signaling molecule related to neuropilins, is synthesized and secreted by photoreceptor cells in the outer retina; then it interacts with inner retinal cells contributing to synaptic organization and optic nerve fiber integrity. We developed an assay to examine how… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
20
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 33 publications
(50 reference statements)
2
20
0
Order By: Relevance
“…In addition, the distribution of retinoschisin protein in chick retina (Fig. 1) is very similar to the pattern described in mammals (8,15,33). These results indicate that retinoschisin is very important in retina function and physiology across species.…”
Section: Discussionsupporting
confidence: 66%
See 3 more Smart Citations
“…In addition, the distribution of retinoschisin protein in chick retina (Fig. 1) is very similar to the pattern described in mammals (8,15,33). These results indicate that retinoschisin is very important in retina function and physiology across species.…”
Section: Discussionsupporting
confidence: 66%
“…We also found that the distribution of retinoschisin protein in the chick retina (Fig. 1A) was similar to that in mammals (8,15,33). The distribution of retinoschisin protein was most prominent on the photoreceptor outer and inner segments (OS/IS), whereas outer and inner plexiform layers (OPL and IPL) also showed heavier staining (Fig.…”
Section: Q G G P N S V W S S G T N S Ttggagtgcatgccagagtgcccctaccacmentioning
confidence: 53%
See 2 more Smart Citations
“…Müller glial cells play a role in distributing RS1 throughout the retina through a process of transcytosis [128]. While RS1 appears to be synthesized by all retinal neurons during development [125], other experiments have shown that retinoschisin, synthesized and secreted into the subretinal space by photoreceptors, is endocytosed by the apical microvilli of Müller cells, which then transport it internally and secrete it throughout the inner and outer retina at its focus sites in the mature retina [49,125,127,128]. This may be a mechanism to supplement retinoschisin expression throughout the retina.…”
Section: Rs1mentioning
confidence: 99%